Reading questioning answering (RQA) method in learning the interaction of living things with their environment: The application to improve students' cognitive learning outcomes - Kasim, Milanda; Latjompoh, Masra; Aydalina, Regina Valentine (Journal of Research in Instructional, 2024)
This study aims to determine the improvement in students' cognitive learning outcomes through the implementation of the Reading Questioning and Answering (RQA) teaching method on the topic of interactions between living organisms and their environment at SMP Negeri 1 Tilango. This research is a pre-experimental study involving only one class as the experimental class. The study was conducted over two sessions. Data were collected using observation and testing techniques. The data analysis techniques used include the analysis of learning implementation, student activity analysis, and cognitive learning outcome analysis. The results of the study indicate that the application of the Reading Questioning and Answering (RQA) teaching method can enhance the cognitive learning outcomes of Grade VII.3 students at SMP Negeri 1 Tilango.